Enhancing Supplier Ealuation and Selection in Supply Chain Using a PROMETHEE-Based Decision-Making Support System - Marzieh Afshari; Hassan Farsijani (مدیریت بهره وری)
Abstract The supplier selection process is considered one of the most relevant decisions in supply chain management owing to its effect on the product quality and buyer performance. Albiet the high volume of investment in Iran automotive industry, and despite the importance of this industry for the national economy, the supplier selection process in this industry has rarely been considered. Considering the importance of the subject, in this research, the supplier evaluation and selection in the supply chain of a company that manufactures automotive plastic parts was conducted for the first time using the PROMETHEE method as a multi-criteria decision-making method. By identifying effective criteria for evaluating and selecting suppliers and integrating them, a comprehensive application model was prepared that can solve the needs of the studied company as a decision-making support system, and can also be generalized as a practical instruction for other industries and similar study subjects. In order to compare and ensure more certainty of the obtained results, the data of this research, in addition to the mentioned method, was also evaluated with the Fuzzy ANP method. The statistical population of the study consists of five suppliers of BL3 polyethylene material, which is used in the manufacture of the "right dashboard air outlet channel" (Dena car) by JAHADIN PARAND Industrial Company. The results obtained from both methods were completely similar and the suppliers of Bakhtar, Maroon, Jam, Arak and Amir Kabir were ranked from first to fifth in both ranking methods.   Key Words: supplier evaluation and selection, Fuzzy ANP, PROMETHEE, multi-criteria decision-making.       1.Introduction The present study seeks to design a robust decision-making support system that offers a comprehensive framework to evaluate and select suppliers within the automotive industry. The purpose of this research is to first identify effective criteria for ranking suppliers, then, by using them, evaluate suppliers employing PROMETHEE (as the main method) and F-A.NP methods, and finally select the best supplier. Based on this, the research topic is focused on analying the ranking of suppliers of Jihadin Parand Industrial Company (a company that manufactures automotive plastic parts) as a case study. The results of this research can help managers and experts who are the decision makers of this company in the process of updating and improving supplier selection while changing and improving the company's strategy. Also, the research structure, methodology, and framework can be useful for researchers and experts interested in evaluating and selecting suppliers for other specific industries. Literature Review Among the studies that have been conducted in recent years pertinet to the supplier evaluation and selection scope in the field of automotive industry, Khatami Firouzabadi and Khodaverdi’s (2012) study is included. They chose the top supplier of the Spring part used in the Tiba car (an Iranian Saipa product) using the Analytical Hierarchy Process (AHP) method. Tahvili Naeeni (2017) has used the multi-criteria decision-making techniques of DEMATEL and VIKOR to evaluate and select the car paint manufacturers in Saipa Automobile Company. Safai Qadikolai et al. (2017) by examining the effective factors in selecting sustainable suppliers in Saipa Company, identified 17 appropriate indicators. Valizadeh and Alizadeh Bermi (2017) evaluated and selected the top exhaust supplier in Iran Khodro company by considering the risk and using the integrated technique of DEMATEL and VIKOR. Rahiminezhad Galankashi et al. (2016) also investigated the issue of supplier selection in the automotive industry using the fuzzy AHP approach. Arab et al. (2018) also identified and leveled suppliers’ resilience criteria at Avrand's Industrial Group supply chain using a combination of Fuzzy Delphi (F-DELPHI) and Interpretative Structural Modeling techniques. Methodology In this research, we intend to use PROMETHE and F-ANP methods to rank the suppliers of a company that manufactures automotive plastic parts. For this purpose, first, the proposed criteria for supplier selection are identified. Then, PROMETHE and F-ANP methods are used to determine the impact of each criterion in the selection and evaluation of suppliers. In order to perform the calculations, the BL3 polyethylene material, which is used in the manufacture of the "right dashboard air outlet channel" (used in the Dana car) by Jihadin Parand Industrial Company, has been selected as a sample. It is possible to get this material from five suppliers and the suppliers of the mentioned material will be evaluated and selected based on the identified criteria. Result In order to evaluate and select the suppliers of Jihadin Parand Industrial Company, seven main criteria and eleven indicators were used, among which, the criteria of cost, quality and delivery as the most important criteria were selected according to the expert opinions of the mentioned company. The measurement quality of this research is 92.6%, which shows the high percentage of reliability of the research and the accuracy of the research process. The ranking done with both PROMETHE and F-ANP methods obtained similar results and showed that among the suppliers of the investigated company (Bakhtar, Maroon, Jam, Arak and Amir Kabir Petrochemicals), Bakhtar alternative has better properties than the others, and that it is the best choice for Jihadin Parand Industrial Company. Conclusion The present research was carried out using the PROMETHEE method to evaluate and select the best supplier in Jihadin Parand Industrial Company that manufactures automotive plastic parts.  Visual PROMETHEE software was used to interpret the ranking of the suppliers. Visual PROMETHEE software is a valuable tool for considering the strengths and weaknesses of all suppliers in all criteria in order to rank and select suppliers. Another well-known multi-criteria method, that is, F-ANP was also used for the decision-making process in this research. The ranking done with both mentioned methods obtained similar results and showed that the Bakhtar supplier is the leader among the five suppliers of Jihadin Parand Industrial Company which has high scores in indicators of product price, quality assurance, order delivery capability, order fulfillment rate and technological capability. Maron Petrochemical was chosen as the second best supplier, the points obtained for this alternative were slightly lower than the Bakhtar alternative, and the road distance was considered as a weakness of this supplier. The third rank belonged to Jam Petrochemical, which showed prominent positive properties in some indicators (quality assurance, order fulfillment rate, and technological capability). Arak Petrochemical was ranked fourth, and the weakest rank belonged to Amir Kabir Petrochemical, which clearly showed negative properties regarding indicators and definitely does not have much chance to be selected by the decision makers of Jihadin Parand Industrial Company. From a managerial point of view, the results of this research can help decision makers to evaluate and correct the alignment between the supplier selection process and the company's strategy in the form of a decision making support system. Conflict of interest: none